PENGARUH LANGUAGE GAMES TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS - Komang Trisnadewi; Eka Ayu Purnama Lestari (Universitas Warmadewa, 2018)
[Title: The Influence of Language Games on Student’s Speaking Ability] In learning a language, especially English, there are many different methods and strategies offered. One of them is using games. This study aims to describe the influence of language games on student’s speaking ability. The subjects of this study are 19 students of class Z STMIK STIKOM Indonesia.The result shows that the application of language games has a positive and significant influence on student’s speaking ability. It includes the pronunciation, fluency, and accuracy. The attention, response, discipline, and student’s participation also increased. Based on the results of the questionnaire, all students agree that language games is very fun and very motivating students to participate more in every activity in the classroom.